2018
DOI: 10.1108/lhs-06-2017-0031
|View full text |Cite
|
Sign up to set email alerts
|

The influence of leadership behavior, organizational commitment, organizational support, subjective career success on organizational readiness for change in healthcare organizations

Abstract: Purpose The purpose of this study is to investigate the influence of leadership behavior, organizational commitment, organizational support and subjective career success on organizational readiness for change in the healthcare organizations. The authors want to determine if nurses who had higher levels of organizational commitment, organizational support and subjective career success relationships were more open and prepared for change. Design/methodology/approach Cross-sectional, descriptive-correlational sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 54 publications
6
27
0
4
Order By: Relevance
“…Social support is an important factor for improving the psychosocial work environment and fostering a positive work climate and is conducive to the acquisition of career achievement (Johnsen et al, 2018;Wang et al, 2018). A good social support system can help nurses to prevent the onset of work-related stress, resolve work difficulties, and provide career planning, which is an important factor for nurses' career development and success (Al-Hussami et al, 2018;Southward and Cheavens, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Social support is an important factor for improving the psychosocial work environment and fostering a positive work climate and is conducive to the acquisition of career achievement (Johnsen et al, 2018;Wang et al, 2018). A good social support system can help nurses to prevent the onset of work-related stress, resolve work difficulties, and provide career planning, which is an important factor for nurses' career development and success (Al-Hussami et al, 2018;Southward and Cheavens, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the critical resources of the FDC are the development of human resources, where trained doctors and commitment from other healthcare workers in the organization are essential for implementing the initiative. Many studies have also shown the importance of leadership and their commitment as the critical success factor of health programs, especially new ones (39)(40)(41). Client input in the form of engagement and education are also equally important, but are often neglected in the process.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements for leadership styles adapted from MLQ 6S [69][70], authorized by Mind Garden. MLQ 6S has been applied in a variety of recent research disciplines and proved to be reliable instruments [71][72][73]. Finally, hardiness Dispositional Scale 15 (DRS 15) was adapted from [74], and authorized by MHS Inc.…”
Section: Instrument Developmentmentioning
confidence: 99%